2000
DOI: 10.1159/000016762
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Carbonic Anhydrase Isozyme VI in the Developing Bovine Parotid Gland

Abstract: The distribution of bovine carbonic anhydrase isozyme VI (CA-VI), purified from bovine saliva, was studied immunohistochemically using antiserum against bovine CA-VI in bovine parotid glands during fetal and postnatal development. A weak expression of CA-VI in undifferentiated epithelial cells and ductal cells was observed in a 4- to 5-month-old fetus with a 26-cm crown-rump length. The reaction in both acinar and ductal cells subsequently persisted during late gestation and birth. Although anti-CA-VI reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 22 publications
(34 reference statements)
2
36
0
Order By: Relevance
“…All preparations were incubated with 0.02% H 2 O 2 and 0.1% diaminobenzidine tetrahydrochloride in 0.05 M Tris-HCl (pH 7.6) for 5 min. Fixation with Bouin's fluids has been found to provide the maximum retention of affinity for the present antibody and the most consistent immunostaining by the previous studies [5].Western blotting: Ten % dodecyl sodium sulfate polyacrylamide gel electrophoresis (SDS-PAGE) was applied in the analyzing of crude extracts from bovine tissues. Briefly, 10 µl samples from crude extracts of bovine colon, rumen and parotid gland, and low-molecular-weight protein marker (Pharmacia, Piscataway, NJ, U.S.A.) were directly boiled in 100 µl SDS-PAGE sample solvent with mercaptoethanol at 100°C for 5 min.…”
mentioning
confidence: 79%
“…All preparations were incubated with 0.02% H 2 O 2 and 0.1% diaminobenzidine tetrahydrochloride in 0.05 M Tris-HCl (pH 7.6) for 5 min. Fixation with Bouin's fluids has been found to provide the maximum retention of affinity for the present antibody and the most consistent immunostaining by the previous studies [5].Western blotting: Ten % dodecyl sodium sulfate polyacrylamide gel electrophoresis (SDS-PAGE) was applied in the analyzing of crude extracts from bovine tissues. Briefly, 10 µl samples from crude extracts of bovine colon, rumen and parotid gland, and low-molecular-weight protein marker (Pharmacia, Piscataway, NJ, U.S.A.) were directly boiled in 100 µl SDS-PAGE sample solvent with mercaptoethanol at 100°C for 5 min.…”
mentioning
confidence: 79%
“…The following findings indicate that this protein is CA-VI: 1) it bound to a sulfonamide inhibitor affinity column, from which it was eluted with carbonic anhydrase inhibitor NaN 3 ; 2) it showed CO 2 hydratase activity; 3) anti-bovine CA-VI serum (produced in our laboratories [1]), crossreacted with the purified protein (data not shown).…”
mentioning
confidence: 90%
“…The molecular mass of the cytoplasmic CA isozymes CA-I, CA-II and CA-III is approximately 30 kDa, whereas that of the CA-VI subunit is roughly 40 kDa (46 kDa, rat; 40-42 kDa, human; 42 kDa, cow) as measured by SDS-PAGE [1,3,10]. Fernley et al [5] reported that the molecular mass of sheep CA-VI is 540 kDa, according to gel filtration under non-denaturing conditions, and that its apparent subunit molecular mass is 45 kDa, as measured by SDS-PAGE.…”
mentioning
confidence: 96%
See 2 more Smart Citations